THE DEVELOPMENT OF STUDENT WORKHEET BASED ON GUIDED INQUIRY ON â€œCOLLISION LABâ€ VIRTUAL EXPERIMENT TO IMPROVE HIGH SCHOOL STUDENT LEARNING OUTCOMES - KHAIRAH NISSA RAHMAWATI, NUR; , MADLAZIM (Inovasi Pendidikan Fisika, 2018)
Abstract The purposes of this study is to create a feasible student worksheet based on guided inquiry on virtual experiment ?Collision Lab? to improve high school student?s learning outcome in Lamongan region. The feasibility of this student worksheet is based on validity, effectifity, and practicality. The research type used is the development research ADDIE model. The result of research shows that validity of the student worksheet over all is 86,28%, categorized as very valid, which include, feasibility of content is 85,42%, feasibility of presentation is 87,50%, feasibility of language is 85,42%, and feasibility of design is 86,81%. This student worksheet is very effective shown in the result of teacher activities is 84,62%, the result of students activities is 90%, and the improvement of student?s learning outcomes by average score gain pre-test and post-test is 0,73 categorized as high. Practicality of this student worksheet is based on student?s response to student worksheet based on giuded inquiry that developed is 98% categorized as exellent. So we can conclude that student worksheet based on guided inquiry on ?Collision Lab? virtual experiment is very feasible and can improve student?s learning outcomes. Keywords: Student Worksheet, Guided Inquiry, Virtual Experiment, Collision Lab, Students?s Learning Outcomes.